Examining the moderating effect of perceived government support on e-business adoption among Omani SMEs - Ahmed, Mahfooz; Al-Riyami, Salim Nasser; Wan Husain, Wan Rohaida; Juhdi, Nurita; Al-Shuwaikh, Fatima; Haji, Ali (Elsevier, 2025)
This study examines the moderating effect of Perceived Government Support (PGS) on the adoption of e-business among Small and Medium Enterprises (SMEs) in Oman, drawing on the Unified Theory of Acceptance and Use of Technology (UTAUT). While prior research has examined the direct influence of UTAUT constructs, fewer studies have considered institutional support as a contextual moderator in developing economies. To address this gap, the present study integrates PGS into the UTAUT model to explore its role in shaping e-business adoption in Oman. A quantitative, cross-sectional survey was conducted with 641 SME owners, managers, and decisionmakers who had benefited from government support programs. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the hypothesised relationships. The results show that Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions significantly influence e-business adoption. More importantly, PGS was found to positively moderate the relationship between Facilitating Conditions and e-business adoption, underscoring the critical role of perceived institutional support in amplifying the enabling environment for digital transformation. The study’s novelty lies in extending UTAUT by incorporating a government-related contextual moderator that reflects the realities of emerging economies. Practically, the findings provide policymakers and SME development agencies with evidence-based insights to design targeted interventions such as infrastructure investment, training, and financial incentives that are especially vital for micro and small enterprises operating under resource constraints.